Inventory of one hectar of a gallery forest - de Paula, José Elias; Encinas, José Imaña; Pereira, Benedito Alísio da Silva (Pesquisa Agropecuaria Brasileira, 1993)
One hectare of gallery forest was surveyed at the Capãozinho stream in Brasília, DF, Brazil. Among others, the following parameters were estimated: volume with bark and dry weight of stem and branches, form, and basal area. Five-hundred and sixty-eight trees with diameter at breast height (DBH) equal to or greater than 5 cm, belonging to 73 species, were measured in the area. The total volume was 170.4436 m3/ha and the total dry weight of wood was 127.49 tons. The species with the most biomass production were: Amaioua guianensis Aublet, Aspidosperma australe M. Arg., Belangera glabra Camb., Callisthene major Mart., Copaifera langsdorffii Desf., Cryptocarya aschaersoniana Mez., Emmotum nitens (Benth.) Miers., Maprounea guianensis Aublet, Ocotea spixiana (Ness.) Mez., Protium brasiliense Engl., e Siphoneugena chnoosepala Kiaersk, and 1,673 specimens of the natural regeneration were registered.